A Bottom‐Up Approach to Red‐Emitting Molecular‐Based Nanoparticles with Natural Stealth Properties and their Use for Single‐Particle Tracking Deep in Brain Tissue. Issue 22 (22nd April 2021) - Rosendale, Morgane; Flores, Jessica; Paviolo, Chiara; Pagano, Paolo; Daniel, Jonathan; Ferreira, Joana; Verlhac, Jean‐Baptiste; Groc, Laurent; Cognet, Laurent; Blanchard‐Desce, Mireille
Abstract: Fluorescent nanoparticles dedicated to bioimaging applications should possess specific properties that have to be maintained in the aqueous, reactive, and crowded biological environment. These include chemical and photostability, small size (on the scale of subcellular structures), biocompatibility, high brightness, and good solubility. The latter is a major challenge for inorganic nanoparticles, which require surface coating to be made water soluble. Molecular‐based fluorescent organic nanoparticles (FONs) may prove a promising, spontaneously water‐soluble alternative, whose bottom‐up design allows for the fine‐tuning of individual properties. Here, the critical challenge of controlling the interaction of nanoparticles with cellular membranes is addressed. This is a report on bright, size‐tunable, red‐emitting, naturally stealthy FONs that do not require the use of antifouling agents to impede interactions with cellular membranes. As a proof of concept, single FONs diffusing up to 150 µm deep in brain tissue are imaged and tracked. Abstract : Fluorescent organic nanoparticles displaying intrinsic stealth properties toward biological membranes are prepared by nanoprecipitation of a hydrophobic, conjugated, red‐emitting quadrupolar dye. The excellent brightness, stability, and size control down to ≈10 nm of these nanoparticles allow for single‐particle tracking deep in brain tissue. These findings point to a novel route for the bottom‐up molecular design of the nano–bio interface.